2020
DOI: 10.1136/bmjopen-2020-040771
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for an implementation study of an evidence-based home cardiac rehabilitation programme for people with heart failure and their caregivers in Scotland (SCOT:REACH-HF)

Abstract: IntroductionDespite evidence that cardiac rehabilitation (CR) is an essential component of care for people with heart failure, uptake is low. A centre-based format is a known barrier, suggesting that home-based programmes might improve accessibility. The aim of SCOT: Rehabilitation EnAblement in CHronic Heart Failure (REACH-HF) is to assess the implementation of the REACH-HF home-based CR intervention in the context of the National Health Service (NHS) in Scotland.This paper presents the design and protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…When comparing patients according to the number of attended sessions (<24 sessions vs. ≥25 sessions), at 1-year and 5-year, mortality rates were shown to be significantly lower for those who attended ≥25 CR sessions (2.2% vs. 5.3% at 1-year, and 16.3% vs. 24.6% at 5-years) (Suaya et al, 2009). To overcome this issue, other CR formats have been proposed and are currently being examined (Jin et al, 2014;Abell et al, 2016;Pio et al, 2019;Abreu et al, 2020;Purcell et al, 2020;Forman et al, 2022). Home-based CR programs may improve both participation and outcomes, especially for patients who are living far from standard supervised programs (Besnier et al, 2021;Vonk et al, 2021;Terbraak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing patients according to the number of attended sessions (<24 sessions vs. ≥25 sessions), at 1-year and 5-year, mortality rates were shown to be significantly lower for those who attended ≥25 CR sessions (2.2% vs. 5.3% at 1-year, and 16.3% vs. 24.6% at 5-years) (Suaya et al, 2009). To overcome this issue, other CR formats have been proposed and are currently being examined (Jin et al, 2014;Abell et al, 2016;Pio et al, 2019;Abreu et al, 2020;Purcell et al, 2020;Forman et al, 2022). Home-based CR programs may improve both participation and outcomes, especially for patients who are living far from standard supervised programs (Besnier et al, 2021;Vonk et al, 2021;Terbraak et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent economic modelling on the basis of the results from the trial confirmed the acceptable cost-effectiveness of the REACH-HF programme, with an ICER of £1,720 per QALY 48 . Given its clinical effectiveness and cost-effectiveness, the REACH-HF programme is now being rolled out into routine care across the UK and the Republic of Ireland to improve access to and uptake of cardiac rehabilitation 49,50 .…”
Section: Major Contemporary Issuesmentioning
confidence: 99%
“…We employed a mixed-method, single arm, pre-post design, collecting both quantitative and qualitative data, and drawing on UK Medical Research Council (MRC) guidance on evaluation of complex interventions. 14,15 CR services in six (of a total of 14) NHS Scotland regional Health Boards were included as early adopter sites: NHS Ayrshire and Arran; NHS Lanarkshire; NHS Forth Valley; and NHS Highland, Orkney, and Shetland (the latter three were combined due to small patient numbers). NHS Greater Glasgow and Clyde sponsored the study, and the West of Scotland Research Ethics Service (20/WS/0038) gave ethical approval.…”
Section: Design and Settingmentioning
confidence: 99%